HUBUNGAN KONSELING KELUARGA BERENCANA (KB) DENGAN PENGAMBILAN KEPUTUSAN PASANGAN USIA SUBUR (PUS) DALAM PENGGUNAAN ALAT KONTRASEPSI - Sari, Silviana Kartika; Suryani, Evi Sri; Handayani, Rohmi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Introduction: Family Planning Program which are embodied in the use of contraception despite the lack of attention should be the determining factor in creating quality family. This sometimes short periods of public participation in family planning program tends to decrease. This is because the way of family planning has not published well, if left there will be a large enough population explosion. Policy to increase family planning programs still need to get attention, mainly on improving the quality of communication skills for family planning counselors in conducting family planning counseling. Purpose: To determine the relationship of Family Planning counseling with decision making Fertile Age Couples in the use of contraceptives tools in the Karang Klesem Village South Purwokerto District Banyumas Regency. Research Methodology: This research uses survey research, analytical and descriptive type conducted a case control approach. The sample in this study were divided into two groups, namely the Fertile Age Couples using contraceptives as many as 88 respondents and Fertile Age Couples groups who are not using contraceptives were 71 respondents. Determination of sampling using stratified random sampling. The analysis in this study using Chi Square. Result: Overall Fertile Age Couples planning acceptors counseling is a number 88 (100.0%) respondents and the majority of non-acceptors of family planning Fertile Age Couples never received family planning counseling of 54 (76.1%) respondents. Based on the analysis, H0 is rejected because it found that the result Ï = 0.000. Conclusion: There was a significant relationship between Family Planning counseling with decision making Fertile Age Couples in the use of contraceptives tools. Suggestion: It is expected that health professionals can better improve the quality of family planning services again to the fertile age pair. Key words : Counseling, Decisions, Fertile Age Couples, Family Planning